Nanoparticles supplementation through foliar feed contributed to the growth and cocoon yield of silkworm (Bombyx mori) - KANNIHALLI, SALEEMALI; RAYAR, S G; MALLAPUR, C P; PATIL, P V; HOSAMANI, RAVIKUMAR (The Indian Journal of Agricultural Sciences, 2024)
An experiment was conducted during 2021–22 and 2022–23 at University of Agricultural Sciences, Dharwad, Karnataka to study the effect of metal nanoparticles on silkworm (Bombyx mori) growth and cocoon yield. The experiment was laid out in completely randomized design (CRD) comprised of 11 treatments with 3 replications. The various concentrations (50, 100 and 200 ppm) of nanoparticles, viz. nano silver, nano zinc and nano copper were extrafoliated to mulberry leaves and were administered to silkworms daily once at morning (first feed) from second day of fifth instar. The study revealed that, silver nanoparticles at 200 ppm concentration emerged as the best supplement with improved larval, cocoon and silk parameters by recording shorter larval duration (616.42 h), fifth instar duration (166.12 h), higher mature larval weight (40.626 g/10 larvae), effective rate of rearing (97.58%), silk productivity (6.225 cg/day), silk gland weight (1.885 g/larva), pupal weight (13.757 g/10 pupae), cocoon yield (794.85 g/dfl), cocoon weight (18.102 g/10 cocoons), shell weight (4.307 g/10 shells), cocoon shell ratio (23.79%), cocoon filament length (948.52 m), finer denier (2.75 d), highest fibroin (80.23%) and lowest sericin protein (19.78%).